Novel incorporation of charged hydroxyapatite nanoparticles into resin adhesive: Novel incorporation of charged hydroxyapatite nanoparticles - Agha, Bahra H.; Hamasaeed, Niaz Hamaghareeb; Hussain, Faiq H. S. (Cellular and Molecular Biology, 2023)
The direct mixing of Nano-hydroxyapatite with Resin Adhesive often leads to weak molecular interactions, which can compromise the dispersion of Nano-hydroxyapatite within the resin adhesive and cause structural damage to the Nano-hydroxyapatite. Therefore, the present study aimed to identify an approach in which Nano-hydroxyapatite is charged or modified prior to its integration into resin adhesive. In this study, Nano-hydroxyapatite was modified using aminopropyltriethoxysilane (APTS), subsequently, the amine groups present on the surface of Nano-hydroxyapatite were additionally modified using succinic anhydride. This modification process resulted in the production of negatively charged Nano-hydroxyapatite - aminopropyltriethoxysilane (n-HA-APTS-SAH). The charged Nano-hydroxyapatite particles were characterized using FTIR and SEM. Subsequently, the charged Nano-hydroxyapatite particles were incorporated into resin dental adhesive. Comprehensive characterization of the composite material was carried out through SEM, FTIR, EDX mapping, and Micro-Raman Spectroscopy. The results revealed the presence of Nano-hydroxyapatite in the mixture and a homogeneous and well-dispersed state with no observable aggregation of Nano-hydroxyapatite particles within the adhesive. Furthermore, the particles still maintain a spherical shape with their sizes falling within the nanoscale range.